2022
DOI: 10.1016/j.paid.2021.111223
|View full text |Cite
|
Sign up to set email alerts
|

Dispositional mindfulness mediates the relationship between conscientiousness and mental health-related issues in adolescents during the COVID-19 pandemic

Abstract: The COVID-19 pandemic is seriously affecting the mental health of adolescents and triggering a series of mental health-related issues. The present study investigates the relationships between conscientiousness, dispositional mindfulness (DM), and adolescents' mental health-related issues including anxiety, depression, and perceived stress during this time. In this study, after obtaining informed consent from participants' parents, 5994 Chinese adolescents voluntarily and anonymously completed an online survey.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…With further research on mindfulness, the relationship between mindfulness as an idiosyncratic trait and emotion prediction has begun to draw people's attention [19]. Studies have shown that trait mindfulness is negatively correlated with perceived stress [20], while emotional exhaustion is just an undesirable consequence of the individual's perceived stress. Therefore, a high level of trait mindfulness may be related to a low level of emotional exhaustion.…”
Section: Trait Mindfulness and Emotional Exhaustionmentioning
confidence: 99%
“…With further research on mindfulness, the relationship between mindfulness as an idiosyncratic trait and emotion prediction has begun to draw people's attention [19]. Studies have shown that trait mindfulness is negatively correlated with perceived stress [20], while emotional exhaustion is just an undesirable consequence of the individual's perceived stress. Therefore, a high level of trait mindfulness may be related to a low level of emotional exhaustion.…”
Section: Trait Mindfulness and Emotional Exhaustionmentioning
confidence: 99%
“…Additionally, excessive information exposure is an important cause of media vicarious traumatization [ 14 ]. According to Nikčević et al’s and Liu et al’s studies, individuals who are high on conscientiousness tend to feel more stress, anxiety, and depression in emergencies, which can lead to psychological problems [ 62 , 63 ]. Moreover, a previous study argued that neuroticism is also a significant driver of vicarious trauma [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The strong self-control exhibited by conscientious individuals drives them to prioritize the execution of their planned strategies over personal interests. Conscientious females may experience higher anxiety levels when their decision-making process lacks proper planning [128,129].…”
Section: Gender × Conscientiousnessmentioning
confidence: 99%